Spatial Analysis to Determine the Geothermal Potential Index: The Case Study of Dieng Geothermal Complex - Dwi Wahyu Hardiyanto; Agung Setianto; Agung Harijoko (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2024)
The exploration is the activity of search areas that have the potential natural resources. Such as the exploration of geothermal potential. It can be using of spatial analysis. Spatial analysis can be base modeling of the geothermal potential in the research area. The analytic hierarchy process (AHP) is a fundamental analysis of the modeling data, where the comparison matrix from the analysis like surface temperature, lineament, and eruption center. The result of modeling in the Dieng volcanic complex has identified as the geothermal potential area. The potential area is around of G. Pakuwaja, G. Pangonan-Merdada, and G. Pagerkandang. So that the integration method of the modeling can be used as the method of the geothermal exploration activities.